2006
DOI: 10.3748/wjg.v12.i37.5964
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hepatitis B virus genotypes: Phylogenetic analysis and virological characteristics of Genotype C circulating among HBV carriers in Kolkata, Eastern India

Abstract: The present study reports the genotypic distribution and the characteristics of partial genome sequences of HBV/C isolates from Eastern India. Low genetic diversity and confinement of HBV/C in Eastern India possibly indicate a recent, limited, spread in this region. Genotype C with T1762/A1764 mutation has been reported to increase the risk for hepatocellular carcinoma; therefore genotype C carriers in Eastern India should be carefully monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 39 publications
10
50
2
1
Order By: Relevance
“…A study conducted by Kumar A et al found that the genotype D was dominant over genotype A and found genotype C in one patient; this genotype has not previously been reported from India [13]. The other studies found genotype D to be the predominant genotype on genotype A [3,10]. Our results are in accordance with the latter studies which showed the dominancy of genotype D on A. HBV genotypes have been shown to have a distinct geographic distribution.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A study conducted by Kumar A et al found that the genotype D was dominant over genotype A and found genotype C in one patient; this genotype has not previously been reported from India [13]. The other studies found genotype D to be the predominant genotype on genotype A [3,10]. Our results are in accordance with the latter studies which showed the dominancy of genotype D on A. HBV genotypes have been shown to have a distinct geographic distribution.…”
Section: Discussionsupporting
confidence: 91%
“…In our study it was observed that in Uttar Pradesh, North India the most prevalent genotype among patients with HBV related chronic liver disease was genotype D (78%) the remaining 22% had genotype A. HBV genotypes A and D have been well documented from different parts of mainland India [3,10,13,27]. There is not much information regarding the prevalence of HBV genotypes from North India.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…4 This population formed clusters distinctly from the North-East population groups (ethnic affiliation to Mongoloid), who are possibly descendents of ancestral population of China. 5 Thus, the history of Bangladesh combines Indo-Aryan, Austro-Asiatic, Dravidian, Mughal, Arab, Persian, Turkic and British influences. 6 There are several ethnic groups in Bangladesh, where 98% are Bengali and the remaining 2% belong to the Chakma, Bawm, Garo, Kiri, Marma, Tipuri and other ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have found that C-terminal truncated S proteins exist in patients with chronic hepatitis B infection and hepatocellular carcinoma [34] . The shorted S proteins can stimulate gene expression from the endogenous HBV enhancer Ⅰ and can also deregulate the expression of oncogenes such as c-myc [35] , which may help clarify the tumor development mechanism of HBV. Whether the truncated S proteins www.wjgnet.com…”
Section: Cacatttcctgmentioning
confidence: 99%